Reinterpreting Qawāmah in Islamic Family Law: Comparative Syaltut-Shahrur Analysis for Gender Justice - Virdausa, Ahmada Rivqy; Adhim, Zakiyuddin Abdul; Mudore, Syarif Bahaudin; Romadhon, Ridho (Program Studi Hukum Keluarga Islam, 2026)
This study examines the concept of qawāmah (family leadership) from the perspectives of Mahmud Syaltut and Muhammad Shahrur and explores. Its relevance to contemporary social realities and Islamic family law in Indonesia. The study is motivated by the ongoing debate regarding gender roles in Muslim families and the growing socio-economic participation of women, which challenge traditional understandings of family leadership. Using a qualitative library research method, this study collects and analyzes data from primary and secondary literary sources related to the thoughts of Syaltut and Shahrur. A comparative approach is employed to identify similarities, differences, and the implications of their interpretations. The findings reveal that Syaltut understands qawāmah as male leadership based on men’s responsibility for family maintenance and protection, while emphasizing justice, consultation, and cooperation between spouses. In contrast, Shahrur reinterprets qawāmah as a functional and conditional role determined by competence, contribution, and responsibility rather than biological sex. The study concludes that although Syaltut’s perspective remains influential within Indonesian legal and social frameworks, Shahrur’s contextual approach offers a more gender-responsive interpretation that accommodates contemporary family dynamics. Family leadership should therefore be understood as a partnership oriented toward achieving sakīnah, mawaddah, and raḥmah.